Peran Pemerintah Daerah dalam Pelestarian Budaya Pasola di Kabupaten Sumba Barat - Jeskhial Marton Raga Namu; Hendrik Toda; David Wilfrid Rihi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Pasola is a traditional cultural ritual of the people of West Sumba Regency, which holds strong historical, social, and spiritual values and also has significant potential as a cultural tourism attraction. However, its sustainability faces several challenges, including the shift from sacred meaning to tourism commodification, limited infrastructure, and suboptimal policy implementation. This study aims to analyze the role of the local government in preserving Pasola culture using the theoretical framework of government roles as regulator, dynamizer, and facilitator. This research employs a qualitative descriptive approach. Data were collected through interviews, observation, and document analysis, and analyzed using the interactive model of Miles and Huberman. The findings indicate that the West Sumba Regency Government has performed its roles relatively well. As a regulator, the government has established regulations, safety standards, and cultural promotion policies. As a dynamizer, it has encouraged community participation through cultural calendars, the formation of cultural preservation teams, and cultural education programs. As a facilitator, the government has provided financial support, infrastructure, health services, and collaboration with the private sector. Nevertheless, challenges remain in terms of policy implementation, particularly regarding safety management, equitable distribution of assistance, infrastructure quality, and consistent application of standard operating procedures. This study concludes that stronger coordination, capacity building, and continuous evaluation are essential to ensure effective, sustainable cultural preservation while maintaining the sacred values of Pasola.